Influence of Dietary Cinnamon Oil Supplementation on Fatty Acid Composition of Liver and Abdominal Fat in Broiler Chicken - Dalkilic, B.; Ciftci, M.; Guler, T.; Cerci, I. H.; Ertas, O. N.; Guvenc, M. (Taylor & Francis Ltd, 2009)
The potential effects of essential oil from cinnamon on fatty acid compositions of liver and abdominal fat in broilers were studied. Two hundred and forty 5-d-old commercial broiler chicks (Ross-308) were divided into 4 equal groups of 60 birds in each and randomly assigned to four treatment diets with four replicates. Experimental groups were; corn-soybean meal basal diet (Control), basal diet supplemented with 10 mg/kg Avilamycin (Antibiotic), 500 or 1000 ppm of cinnamon oil (C500, C1000). Poly unsaturated fatty acid (PUFA), omega-3 and omega-6 fatty acid levels of liver lipids were found higher but saturated fatty acid (SFA) levels were found lower in cinnamon oil added groups. The lowest mono unsaturated fatty acid (MUFA) level and the highest SFA level of abdominal fat were found in control group. Supplementation of cinnamon oil to diets could be considered as a natural alternative for producing poultry meat with more desirable PUFA.
Keywords: Broiler; cinnamon oil; fatty acid composition; liver; abdominal fat